Association of Birth Parameters with Refractive Status in a Sample of Caucasian Children Aged 4–17 Years - Berna Akova-Budak; Sertaç Argun Kıvanç; Osman Okan Olcaysü (Journal of Ophthalmology)
Purpose. To investigate the association of birth parameters with refractive status in different age groups of Caucasian children. Materials and Methods. This cross-sectional study included 564 eyes of 282 children aged 4 to 17 years. All children underwent complete ophthalmologic examination. The children were divided into three groups according to their refractive status (emmetropia,myopia, and hyperopia), ages (4–7, 8-9, 10–12, and 13–17), and appropriateness for gestational age, respectively. Results. The mean age of the children was 9.2±2.8 (age range 4–17 years). The mean spheric equivalent was +0.3±1.7 (range: (−10.0)–(+10.0) diopters). The mean birth weight and gestational age were 2681.1±930.8 grams (750–5000 grams) and 37.2±3.7 weeks (25–42 weeks). According to multinominal logistic regression analysis, children with myopia were more likely to have higher birth weights than emmetropic children (OR: 1.0, 95% CI: 1.000–1.001, and P=0.028). The hypermetropes were found to be significantly small for gestational age between 13 and 17 years of age. Conclusion. Birth weight and appropriateness for gestational age as birth parameters may have an impact on development of all types of refractive errors. The hypermetropic children tended to be small for gestational age.